Conectividade de sedimentos em grande bacia hidrográfica: uma comparação com a modelagem de sedimentos - Barreto, Geraldo Andre Rosseto (2023)
Sediment connectivity is a concept that has been widely accepted for the analysis of sediment flow in river basins, and it can be defined as the transfer of sediments within a system, through their disaggregation and transport, from a source to a downstream area. However, the application of Connectivity Indices has typically been applied in smaller basins, ranging from 10 km² to 150 km². On the other hand, mathematical models allow for the representation of hydrological processes and sediment transport across river basins, either with the specific purpose of predicting sediment yield or for analyzing processes and their interactions. These two forms of analysis can be complementary; however, a comparison of mathematical model results with the Connectivity Index is still in its early stages. Thus, this study aims to evaluate the correlation potential of the MGB-SED model with the concept called lateral sediment connectivity, which represents the possibility of sediment released at a certain location on a slope reaching a specific deposition point or channel, considering the slope's morphology in the Doce River basin. For the analysis of sediment yield and transport in the Doce River basin, the MGB-SED model was employed, and for the assessment of lateral sediment connectivity, the Borselli Connectivity Index was used. The correlation between the models was evaluated using the Spearman correlation coefficient. The results indicated that the greatest soil losses occur in mountainous areas with a predominance of pasture, and there is a clear correlation between soil loss and solid discharge, indicating a direct relationship with sediment transport in the drainage network. The spatial distribution of the Connectivity Index indicates that the highest values of this index are associated with the dissected plateaus in the central-southern part of the basin, with the highest IC values identified in areas with varying altitudes and greater anthropogenic use. It was found that lateral sediment connectivity exhibits a complex and variable spatial distribution in the study area. The comparison between the results of the MGB SED model and the lateral sediment connectivity index revealed a low Spearman correlation between all variables obtained by the model, which can be attributed to several reasons, including the distinction in the way the topography and land use of the study area are used in the models, as well as the spatial resolution of the digital elevation model, which may have a greater impact on IC results. This study represents a significant advancement in the understanding of connectivity in a large river basin, however, there is still much to be explored in this research area.